PERANCANGAN BALANCED SCORECARD PERSPEKTIF LEARNING AND GROWTH UNTUK MENINGKATKAN HUMAN CAPITAL VALUE AXA MANDIRI - Amandalisha Panji Amoryandina; Wiyono Pontjoharyo (Perpustakaan Universitas Surabaya, 2018)
Abstract - Generally, entities will measure their employee performances simply using one method, which is financial perspective. That term was changed when Kaplan and Norton bring a new concept called Balanced Scorecard which measuring employees performances not only using single, but forth perspective at once. Using Balanced Scorecard, entities could maximize their strength. Before an entity applying Balanced Scorecard, they need to make plan since Balanced Scorecard are function to describe relationship between action and future entity’s plan. Moreover, the design will be built based on phase; assessment, strategy, objectives, strategy map, measurement, and initiatives. This research will focus on assessing strategic management system on AXA’S sales department using Balanced Scorecard, especially on learning and growth perspective.